The Relationship between Demographic Characteristics with Information and Communication Technology and Empowerment in General Organizations (Case Study: Sari Municipality) - Malafe, Neda Sharifi Asadi; Ahmadi, Masoud; Baei, Fahime (International Review of Management and Marketing, 2017)
This study was an attempt to investigate the relationship between demographic characteristics with ICT and empowerment of Sari municipality staff in 2015. "Research Methodology" in this study was descriptive and correlational. To fulfill the purpose of this study, 152 staff were selected from among a total number of 250 population based on stratified sampling using Krejcie & Morgan sampling table. "The data collection tools" consisted of two standard questionnaires, including ICT questionnaires (%96 validity) and empowerment questionnaire (87% validity). "The data analysis method" was inferential statistics conducting by SPSS. "The results" showed that there was not a significant difference between the mean of ICT and empowerment components among Sari municipality staff in terms of their age, gender, education, work experience, and organizational post. Keywords: Information and Communication Technology (ICT), Knowledge Management, Demographic Characteristics JEL Classifications: E37, E32, C53, C5